Pengembangan Media Pembelajaran Smart Booklet untuk Meningkatkan Hasil Belajar Siswa pada Pelajaran IPAS Kelas V - Nugraha, Adi Tria; Putra, Galih Mahardika Chirstian (FONDATIA, 2024)
The research aims to develop media design, feasibility and effectiveness of smart booklet learning media to improve learning outcomes for class V students at SD Negeri 01 Sampiran. This research uses the Borg and Gall Development model. The research population was 45 people, consisting of 9 class V students as small-scale test subjects and 36 class V students at SD Negeri 01 Sampiran. Data is collected through tests (pretest & posttest) and non-tests such as observations, questionnaires, interviews, and documentation. Validation by material experts reached 80%, while media experts reached 96%. The research results show that smart booklet learning media is effective in improving student learning outcomes, as evidenced by an increase in the average score from 67 to 91, as well as an N-gain test value of 0.713. This shows a high increase in learning. Positive responses were also seen from the questionnaires distributed to teachers and students. In conclusion, the product in the form of smart booklet media is suitable and practical for use in science learning.